Talent selection and genetics in sport - Ozveren, Y.; Oczaldiran, B.; Durma, B.; Oral, O. (Turkish Journal of Sport and Exercise, 2014)
Whether the performance demonstrated by talented sportsmen is hereditary or acquired later has become subject of research for physical education and sport scientists from past to present. However, training science and trainers wonder how far can reach the higher performance limits emerging as a result of talents available in sportsmen. Studies carried out suggested that the concept of higher performance comes true with aggregated environmental and genetic factors. The aim of our study is to discuss the role played by genetics on the differences in performance of sportsmen and selection of sportive talent.